Influence of Fluorine Doping of Activated Carbon Fibers on Their Water Vapor Adsorption Characteristics - Velasco, Leticia F.; Kim, Kyung Hoon; Lee, Young-Seak; Lodewyckx, Peter (Frontiers in Chemistry, 2021)
The characterization of fluorinated carbon fibers by water sorption has been broadly investigated in this work. In brief, a pitch-based activated carbon fiber (ACF) was submitted to a fluorination process under different conditions of partial pressure (F2:N2 ratio) and temperature. This led to samples with varied fluorine content and C-F type bonding. The effect of the fluorination treatment on the textural properties of the ACF was studied by means of nitrogen and carbon dioxide adsorption at -196 and 0°C, respectively, while the changes induced in the surface chemistry of the materials were analysed by XPS. Also, the affinity and stability of the materials towards water was evaluated by single and cycling isotherms. The obtained results show that a mild fluorination not only can preserve most of the textural properties of the parent ACF, but enhance the water uptake at the first stages of the water sorption process, together with a shift in the upswing of the water isotherms towards lower relative humidities. This indicates that fluorination under certain conditions can actually enhance the surface hydrophilicity of carbon materials with specific properties. On the contrary, higher partial pressures led to highly fluorinated fibers with lower porosity and more hydrophobic character. Moreover, they presented a lower chemical stability as demonstrated by a change in the shape of the water isotherms after two consecutive measurements. The kinetics of water sorption in the ACFs provided further insights into the different sorption phenomena involved. Hence, water sorption can definitely help to tailor the water affinity, stability and performance of fluorinated porous carbon materials under humid conditions.